Determination of the young’s modulus of miniaturized cantilever by measuring micro- eflection using the phase-shift shadow moiré method / Lim Jiunn Hsuh, Mani Maran Ratnam, Ong Jiunn Chit and Chiang Ee Pin - Lim, Jiunn Hsuh; Ratnam, Mani Maran; Ong, Jiunn Chit3 (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
This paper presents a measurement for micro-deflection of miniaturized cantilever using phase-shift shadow moiré (PSSM) method and determines the Young’s modulus of the cantilever material. The measurement equipment is calibrated by measuring and comparing the known surface profile of a cylinder with the results from PSSM. The calibration shows that PSSM technique applied has the measurement error of 6 μm. The PSSM method is then applied to measure the micro-deflection of a miniaturized cantilever. The cantilever has the dimensions of 6.49 mm x 0.96 mm x 0.16 mm and the Young’s modulus is unknown. The Young’s modulus of the cantilever material is estimated from theory by using the measured deflection profile. Both the measured and estimated deflection profile are plotted to check for any discrepancy. The comparison shows that the measured deflection profile is similar to the estimated deflection profile. Therefore, the Young’s modulus of the cantilever is estimated to be 60.65 GPa with the uncertainty of ±2.66GPa. The experiment presented in this paper shows the procedure and method to measure the deflection of a miniaturized cantilever and estimate the unknown Young’s modulus.